LncRNA-NEF antagonized epithelial to mesenchymal transition and cancer metastasis via cis-regulating FOXA2 and inactivating Wnt/[beta]-catenin signaling - Liang, Wei-Cheng; Ren, Jia-Lin; Wong, Cheuk-Wa; Chan, Sun-On; Waye, Mary Miu-Yee; Fu, Wei-Ming; Zhang, Jin-Fang (Oncogene, 2018)
Emerging evidence indicates that the long noncoding RNAs extensively participate in cancer progression. Nevertheless, the molecular pathogenesis of how these lncRNAs regulate tumorigenesis has not been fully elucidated especially in hepatocellular carcinoma (HCC). Here, we sought to define the role of a novel lncRNA named lncRNA-NEF in modulating epithelial to mesenchymal transition (EMT) in HCC. It was found that the lncRNA-NEF was transcriptionally activated by EMT suppressor FOXA2 and frequently downregulated in HCC cell lines as well as clinical specimens. Although enhanced expression of lncRNA-NEF did not affect tumor cell growth, ectopic expression of lncRNA-NEF significantly suppressed EMT program and cell migration. Animal studies validated that lncRNA-NEF alleviated in vivo tumor metastasis and protected mice from tumor-induced mortality. Interestingly, we verified that lncRNA-NEF acted as a novel activator of its neighbor gene FOXA2, which formed a positive feedback loop. Subsequent studies revealed that lncRNA-NEF physically interacted with [beta]-catenin to increase the binding of GSK3[beta] with [beta]-catenin and therefore promoted the inhibitory phosphorylation of [beta]-catenin, leading to the suppression on Wnt/[beta]-catenin signaling and activation of FOXA2 expression. Hence, our findings illustrated a novel feedback loop including FOXA2 and its neighboring gene lncRNA-NEF, which might provide mechanistic insights into the metastatic progress of HCC.